2012 European Frequency and Time Forum 2012
DOI: 10.1109/eftf.2012.6502435
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of Group Delay Variations on GNSS time and frequency transfer

Abstract: Group Delay Variations (GDVs) are azimuth and elevation dependent code delays that can limit the accuracy of the GNSS code observables. This contribution focuses on the GDV determination and discusses several solutions with respect to repeatability and separability. On-site tests at a laboratory network as well as simulations of several time links are discussed analyzing the stochastic processes apparently introduced by GDV. The stability of the P3 links are not effected. However, offsets up to 0.6 ns can occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The GDV corrections for GPS satellite and receiving antennas obtained in this paper refer to a set of reference antennas and are, thus, relative by their nature. One way to achieve absolute corrections of receiving antennas are robot calibrations as demonstrated by Wübbena et al (2008) and Kersten et al (2012). It is desirable to combine both techniques to achieve sets of absolute corrections for GPS receiving and satellite antennas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GDV corrections for GPS satellite and receiving antennas obtained in this paper refer to a set of reference antennas and are, thus, relative by their nature. One way to achieve absolute corrections of receiving antennas are robot calibrations as demonstrated by Wübbena et al (2008) and Kersten et al (2012). It is desirable to combine both techniques to achieve sets of absolute corrections for GPS receiving and satellite antennas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous GDV studies revealed significant azimuth-dependent variations for GPS satellite antennas (Haines et al 2004) and azimuth-dependent GDV of receiving antennas could be demonstrated by Kersten et al (2012). Nevertheless, in this first attempt to determine GDV we preferred to work with a simpler model which only takes nadir-or elevationdependent GDV into account.…”
Section: Code Analysis Based On Mp Observablementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both airborne multipath and antenna group delay variations were found to be primarily biaslike and should be treated as such in the aircraft position protection level equations. These conclusions apply to the current Ground Based Augmentation System (GBAS), the Space Based Augmentation System (SBAS), and future Advanced Receiver Autonomous Integrity Monitoring (ARAIM) concepts [8], as well as precise time transfer applications [9].…”
Section: Introductionmentioning
confidence: 99%